Lysozyme activity and nitroblue-tetrazolium reduction in leukaemic cells. Issue 1 (January 1973) - Catovsky, D.; Galton, D. A. G.
Abstract : The cytochemical methods for lysozyme and nitroblue-tetrazolium reduction have been used to study the blast cells of acute myeloid leukaemia. Both proved useful in characterizing the cases with predominant monocytic differentiation. The demonstration of lysozyme activity helped to define two main groups: (a) with predominantly lysozyme-negative cells (myeloblastic-promyelocytic), and (b) with considerable numbers of positive cells (monoblastic-monocytic). In addition this test was also of value in the differentiation of other leukaemic disorders. Reduction of nitroblue-tetrazolium was also a feature of monocytic differentiation. The combination of these two methods with those for myeloperoxidase and non-specific esterase activity contributes to the cytological characterization of acute myeloid leukaemia.